2016
DOI: 10.1007/s10926-016-9627-4
|View full text |Cite
|
Sign up to set email alerts
|

Vocational Rehabilitation of Transition-Age Youth with Disabilities: A Propensity-Score Matched Study

Abstract: Objective To investigate the employment outcomes of vocational rehabilitation (VR) services for youth with disabilities in a targeted, enhanced, and contract-based secondary transition program as compared to the traditional VR transition services. Methods A population-based study was conducted on 4422 youth with physical, intellectual, learning, mental and hearing disabilities aged 14-21 at application and whose case was closed after receiving VR transition services in a Midwestern state. Selected youth were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…While not included in the analysis, our secondary search of non-randomized vocational interventions identified two studies that highlight key components for supporting people with autism and/or intellectual disability [83,84]. For example, Langi et al found specialized transition programs that integrated school and community-based training within work places, that were delivered during and after secondary school, were more effective than TVR in helping young people disability, including those with intellectual disability, obtain employment outcomes [83]. Similar to the RCTs for young people with autism included in our systematic review analysis, key components of effective programs included job-readiness development, job-shadowing, on-the-job training and support, funded work experience, and job coaching [83].…”
Section: Discussionmentioning
confidence: 99%
“…While not included in the analysis, our secondary search of non-randomized vocational interventions identified two studies that highlight key components for supporting people with autism and/or intellectual disability [83,84]. For example, Langi et al found specialized transition programs that integrated school and community-based training within work places, that were delivered during and after secondary school, were more effective than TVR in helping young people disability, including those with intellectual disability, obtain employment outcomes [83]. Similar to the RCTs for young people with autism included in our systematic review analysis, key components of effective programs included job-readiness development, job-shadowing, on-the-job training and support, funded work experience, and job coaching [83].…”
Section: Discussionmentioning
confidence: 99%
“…Exact matching on selected covariates and propensity score matching methods [14,19] are the most commonly used. These methods are widely used in economics and social sciences, and have been applied to rehabilitation [20][21][22]. Our variable of interest is the Average Treatment effect on the Treated (ATT).…”
Section: Matching Techniquesmentioning
confidence: 99%
“…Predictive factors, such as high parental expectations for youth holding a job after high school graduation, family involvement, life skills instruction, interagency involvement, communication skills, independent living skills, job skills training, social skills, and early work experience, are all correlated with postschool employment of youth with disabilities (Carter et al, 2011;McDonnall, 2011;Wehman et al, 2015). Recently, research regarding the role of early work experience in postsecondary employment outcomes has begun to shift from simply identifying associated factors toward investigating causal relationships between specific interventions and employment outcomes (Balcazar et al, 2018;Fraker et al, 2018;Langi et al, 2016;Luecking et al, 2018).…”
Section: Background and Purposementioning
confidence: 99%